2014
DOI: 10.1016/j.tranon.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Surgical Tumor Tissues, Biopsy, or Cytology Samples for Epidermal Growth Factor Receptor Mutation Testing in Non–Small Cell Lung Carcinoma Based on Chinese Population

Abstract: BACKGROUND: Epidermal growth factor receptor (EGFR) mutation status is crucial in treatment selection for non–small cell lung cancer (NSCLC) patients; however, the detection materials’ availability remains challenging in clinical practice. In this study, we collected surgical resection tissues, lymph node biopsy, and cytological samples for EGFR mutation testing and investigated the associations between gene mutation and clinical characteristics. METHODS: Two hundred and seventy-six NSCLC adenocarcinoma specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Primary and metastatic site biopsies from B+/T-and B+/T+ groups predicted a better response to EGFR-TKIs than biopsies from the B-/T+ group; however, this trend did not apply to resected tissues. Resected samples from early-stage surgeries may have different biological and genetic characteristics compared with advanced-stage metastatic tumor cells (24,25). Another important factor is that adjuvant chemotherapy may influence EGFR mutation status (18).…”
Section: Pfs Time Months ----------------------------------------mentioning
confidence: 99%
“…Primary and metastatic site biopsies from B+/T-and B+/T+ groups predicted a better response to EGFR-TKIs than biopsies from the B-/T+ group; however, this trend did not apply to resected tissues. Resected samples from early-stage surgeries may have different biological and genetic characteristics compared with advanced-stage metastatic tumor cells (24,25). Another important factor is that adjuvant chemotherapy may influence EGFR mutation status (18).…”
Section: Pfs Time Months ----------------------------------------mentioning
confidence: 99%
“…Moreover, genetic alterations within the tumours change the molecular marker profile during the course of the disease. Currently, most advanced NSCLC patients are diagnosed using biopsies or cytology specimens, due to a lack of availability of resected tumour tissue [5]. However, in many patients, adequate diagnostic sampling is problematic, both de novo and post-EGFR therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that the mutation frequency of EGFR mutated patients is closely relevant to tumor node metastasis (TNM) staging, especially to lymphatic metastasis, and the drug-resistant mutation of T790M occurs most commonly in advanced lung cancer. 21,22 A meta-analysis containing 27 retrospective studies and 6950 lung cancer patients revealed that the frequency of echinoderm microtubule associated protein like 4-anaplastic lymphoma kinase (EML4-ALK) gene fusion in advanced lung cancer is significantly higher than in early stage. 23 Data from a study of wholegenome sequencing in Asian patients demonstrated a large difference in genetic background between early and advanced lung cancer.…”
Section: Introductionmentioning
confidence: 99%